PUMP unveiled 21 books - Shalfarina, Shahriman (Penerbit UMP, 2015)
Kuantan: Universiti Malaysia Pahang Publisher (PUMP) unveiled 21 books written by lecturers and staff from various faculties and responsible centres (PTJ) in conjunction with the Quality and Innovation Day here recently.